Crystallographic and spectroscopic characterization of a molecular hinge: Conformational changes in bothropstoxin I, a dimeric Lys49 phospholipase A2 homologue - da Silva Giotto, M. T.; Garratt, R. C.; Oliva, G.; Mascarenhas, Y. P.; Giglio, JR; Cintra, ACO; de Azevedo, W. F.; Arni, R. K.; Ward, R. J. (Wiley-Blackwell, 1998)
Bothropstoxin I(BthTX-I) from the venom of Bothrops jararacussu is a myotoxic phospholipase A2 (PLA2) homologue which, although catalytically inactive due to an Asp49-->Lys substitution, disrupts the integrity of lipid membranes by a Ca2+-independent mechanism, the crystal structures of two dimeric farms of BthLTX-I which diffract X-rays eo resolutions of 3.1 and 2.1 Angstrom have been determined, the monomers in both structures are related by an almost perfect twofold axis of rotation and the dimer interfaces are defined by contacts between the N-terminal alpha-helical regions and the tips of the beta-wings of partner monomers. Significant differences in the relative orientation of the monomers in the two crystal forms results in open and closed dimer conformations, Spectroscopic Investigations of BthTX-I in solution have correlated these conformational differences with changes in the intrinsic fluorescence emission of the single tryptophan residues located at the dimer interface, the possible relevance of this structural transition in the Ca2+-independent membrane damaging activity is discussed. (C) 1998 Wiley-Liss, Inc.
Keywords: venom toxin; protein-membrane interaction; X-ray diffraction; spectroscopy; quaternary structural change